KOMUNIKASI POLITIK PADA POLITIK GLOBAL MELALUI PROPAGANDA PERANG DALAM VIDEO GAME COMMAND AND CONQUER: GENERAL - Sutrisno; Nurfalah, Farida (Universitas Swadaya Gunung Jati, 2024)
Political communication has expanded into the virtual world through video games, as seen in Command & Conquer: Generals. This research uses online qualitative methods with a text analysis approach and semiotic theory to identify meaning in the game. The results of the study reveal the aim of the game to highlight the strength of the post-collapse of the Soviet Union, position the Islamic world as terrorists, and legitimize the US attack on Iraq. This game also utilizes the global scenario after the 9/11 WTC incident, showing the Arab region as a terrorist base for control of oil fields. Arms sales are also shown to be a source of profit, both to the GLA and to Middle Eastern countries involved in the conflict. The following research will focus on political communication models in the 2024 Republic of Indonesia presidential election and the development of political communication applications until 2026. Keywords: Video games, Political Communication, Global Politics, Propaganda, Command and Conquer: Generals, Semiotics